Metabolism of Innate Immune Cells in Cancer - Talty, Ronan (Cancers (Basel), 2021)
SIMPLE SUMMARY: Both cancer cells and immune cells depend on specific metabolic programs for their survival and function. Depending on which metabolic changes occur, immune cells can either promote or suppress the antitumor immune response. This review summarizes the metabolic pathways that polarize innate immune cells for immune activation or suppression and describes the current clinical applications of these findings. ABSTRACT: Cancer cells possess specific metabolic requirements for their survival, proliferation, and progression. Within a shared microenvironment, immune cells depend on competing metabolic pathways for their development and effector function. As a result, local acidification, hypoxia, and nutrient depletion in the tumor microenvironment can alter the antitumor immune response and even promote resistance to immunotherapies such as immune checkpoint blockade and adoptive cell transfer. Although T cells are the primary effectors of the antitumor response, growing evidence demonstrates that innate immune cells are critical to successful tumor clearance. This review aims to summarize current research related to the innate immune system, metabolism, and cancer. We first discuss the specific metabolic requirements of innate immune cells for immune activation and suppression and conclude by highlighting ongoing clinical applications of these findings.